Fish Farmers’ Information Needs: Implications for Fisheries Extension - Salas, Shalumol; Ojha, S. N.; Vipinkumar, V. P.; Dona, P. (Fishery Technology, 2019)
The farming community requires an offset of varied information for their day to day agricultural activities. Assessing farmers information needs is an important aspect of any endeavour aimed to enhance the availability of, and access to information among farmers. The study investigated the information needs of farmers engaged in fish farming in Alappuzha district, Kerala State. A wellstructured and pre-tested interview schedule was used to collect information from sixty randomly selected fish farmers from two fish farmers’ agencies in the area. The identified needs were ranked in terms of weighted score. Information on extension service providers, emerged as the most needed information among the respondents. The recommendations of the study are given for developing and implementing extension service and delivery mechanism with relevant modification and redesigning of available technologies and setting up of awareness and capacity building programmes for fish farmers regarding aquaculture farm information and related needs.